Ecology of Indo-Pacific Humpback Dolphin (Sousa chinensis) and Irrawaddy Dolphin (Orcaella brevirostris) in the Matang mangrove and adjacent coastal waters in Peninsular Malaysia / Kuit Sui Hyang - Kuit , Sui Hyang (2021)

(untitled)
The coastal waters of Matang in Perak, Peninsular Malaysia, are internationally designated as the Matang Mangroves and Coastal Waters Important Marine Mammal Area (IMMA) by the International Union for Conservation of Nature (IUCN). As ecological baseline data were lacking on coastal delphinids that are threatened by anthropogenic activities, this Ph.D. study was conducted to contribute new scientific knowledge and critical understanding of the animals’ ecology in the coastal waters of Matang. Boat-based surveys were conducted from 2013 to 2016, while interview surveys with local fishers were conducted from 2014 to 2017 to determine the abundance, distribution and habitat characteristics, movement and ranging patterns, and human-dolphin interactions of Indo-Pacific humpback dolphins (Sousa chinensis) and Irrawaddy dolphins (Orcaella brevirostris). The abundance estimates of Irrawaddy dolphins in Matang were 763 individuals (CV = 13.3%; 95% CI = 588-990), estimated via line-transect distance sampling. Annual abundance estimates of Indo-Pacific humpback dolphins (hereafter humpback dolphins) via mark-recapture fluctuated from 138 individuals (95% CI = 118-162) in 2013-2014 to 171 individuals (95% CI = 148-208) in 2014-2015, to 81 individuals (95% CI = 67-98) in 2015-2016, likely due to the presence of offshore individuals that moved in and out of the study area. The humpback dolphins exhibited a clustered distribution and were mostly found closer inshore in the shallow estuarine waters and riverine waterways that are less than 10 m deep. The Irrawaddy dolphins had a relatively homogenous distribution and were mostly found in farther coastal waters that are less than 15 m deep. The core areas of feeding and nursery grounds of humpback dolphins were mainly in the estuaries of Kuala Sangga Besar, Kuala Larut and Kuala Jarum Mas. As for Irrawaddy dolphins, the core areas of feeding and nursery grounds were mainly around the coastal waters off Kuala Larut and Kuala Trong. The core areas of these two species overlapped minimally, and likely reflected the distribution of preferred prey resources, species interactions, their differential responses to anthropogenic activities and species dominance. The Minimum Convex Polygon (MCP) ranges of 13 inshore resident humpback dolphins overlapped considerably in the estuaries, where the animals remained within 7 km from shore with a mean MCP range of 217.4 ± 65.2 km2. This ranging pattern in the estuaries is most likely linked to their use of the productive estuarine habitats by optimizing the exploitation of their estuarine prey aggregations that are tidal-driven. Out of 198 local fishers interviewed, 14% (n = 28) had cetacean bycatch that mostly occurred in gillnets and trawl nets. The prevalence of anthropogenic injuries in Irrawaddy dolphins (28.5%) and humpback dolphins (16.5%) also indicated interactions with fishing gears that could threaten their survival. A bycatch risk assessment (ByRA) revealed medium to high dolphin bycatch risk in gillnets and trawl nets throughout most of the study area. This study established important baseline information for future studies to identify abundance trends and habitat shifts, and identified areas that should be prioritized for conservation and habitat management.